Optical characterization of single plasmonic nanoparticles. (30th June 2014) - Olson, Jana; Dominguez-Medina, Sergio; Hoggard, Anneli; Wang, Lin-Yung; Chang, Wei-Shun; Link, Stephan
Abstract : This review surveys the optical properties of plasmonic nanoparticles, and describes techniques used in the optical measurements of single nanoparticles. Abstract : This tutorial review surveys the optical properties of plasmonic nanoparticles studied by various single particle spectroscopy techniques. The surface plasmon resonance of metallic nanoparticles depends sensitively on the nanoparticle geometry and its environment, with even relatively minor deviations causing significant changes in the optical spectrum. Because for chemically prepared nanoparticles a distribution of their size and shape is inherent, ensemble spectra of such samples are inhomogeneously broadened, hiding the properties of the individual nanoparticles. The ability to measure one nanoparticle at a time using single particle spectroscopy can overcome this limitation. This review provides an overview of different steady-state single particle spectroscopy techniques that provide detailed insight into the spectral characteristics of plasmonic nanoparticles.